Developing the principles of chair based exercise for older people: a modified Delphi study - Robinson, Katie R; Leighton, Paul; Logan, Phillipa A.; Gordon, Adam L.; Anthony, Kevin; Harwood, Rowan H.; Gladman, John R.F.; Masud, Tahir (BioMed Central, 2014)
Background Chair based exercise (CBE) is suggested to engage older people with compromised health and mobility in an accessible form of exercise. A systematic review looking at the benefits of CBE for older people identified a lack of clarity regarding a definition, delivery, purpose and benefits. This study aimed to utilise expert consensus to define CBE for older people and develop a core set of principles to guide practice and future research.